Functional conservation and divergence of arabidopsis VENOSA4 and human SAMHD1 in DNA repair - Raquel Sarmiento-Mañús; Sara Fontcuberta-Cervera; Kensuke Kawade; Akira Oikawa; Hirokazu Tsukaya; Víctor Quesada; José Luis Micol; María Rosa Ponce (Heliyon)
The human deoxyribonucleoside triphosphatase (dNTPase) Sterile alpha motif and histidine-aspartate domain containing protein 1 (SAMHD1) has a dNTPase-independent role in repairing DNA double-strand breaks (DSBs) by homologous recombination (HR). Here, we show that VENOSA4 (VEN4), the probable Arabidopsis thaliana ortholog of SAMHD1, also functions in DSB repair by HR. The ven4 loss-of-function mutants showed increased DNA ploidy and deregulated DNA repair genes, suggesting DNA damage accumulation. Hydroxyurea, which blocks DNA replication and generates DSBs, induced VEN4 expression. The ven4 mutants were hypersensitive to hydroxyurea, with decreased DSB repair by HR. Metabolomic analysis of the strong ven4-0 mutant revealed depletion of metabolites associated with DNA damage responses. In contrast to SAMHD1, VEN4 showed no evident involvement in preventing R-loop accumulation. Our study thus reveals functional conservation in DNA repair by VEN4 and SAMHD1.